The Role of Intellectuals in the Making of American Foreign Policy in the Middle East: The Case of Bernard Lewis and the 2003 U.S.A. Invasion of Iraq - El Muhtaseb, Lamis (Dirasat: Human and Social Sciences, 2020)
This paper looks into the dynamics of American foreign policy making in the Middle East concentrating on the role played by intellectuals in this process. The most important and most debated role has been that of the famous British American historian and Orientalist, Bernard Lewis, and his ties with and influence on the Bush administration at the time of the U.S.A. invasion of Iraq in 2003. The main argument is that the misconceptions promoted by Bernard Lewis about the Middle East and his Orientalist approach to the region has provided an intellectual rhetorical justification that ‘legitimized’ the U.S.A. invasion of Iraq in the name of spreading democracy and saving Arabs from tyranny.